2022
DOI: 10.1021/acsaelm.2c00459
|View full text |Cite
|
Sign up to set email alerts
|

Functional Carbon and Silicon Monolayers in Biphenylene Network

Abstract: We investigated the effects of vacancy, void, substitutional impurity, isolated adsorption of selected adatoms, and their patterned coverage on the physical and chemical properties of metallic carbon and silicon monolayers in a biphenylene network. These monolayers can acquire diverse electronic and magnetic properties to become more functional depending on the repeating symmetry, size of the point defects, and on the type of adsorbed adatoms. While a carbon monovacancy attains a local magnetic moment, its voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…These functional properties are tunable by the coverage of diverse adatoms, by the formation of vacancy and other point defects. 20 Other properties related with C ohs have been reported in recent papers. 21,22 In this study, we show that on a 2D monolayer one can realize a number of crucial electromagnetic device functions.…”
Section: ■ Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These functional properties are tunable by the coverage of diverse adatoms, by the formation of vacancy and other point defects. 20 Other properties related with C ohs have been reported in recent papers. 21,22 In this study, we show that on a 2D monolayer one can realize a number of crucial electromagnetic device functions.…”
Section: ■ Introductionmentioning
confidence: 81%
“…Recently, the synthesis of this 2D nonhexagonal, monolayer structure (which consists of the adjacent octagon- ( o ), hexagon- ( h ), and square- ( s ) rings and is specified briefly as C ohs structure in this text) have been realized using different processes. , Even if the 3-fold coordination of atoms is maintained in this new allotrope, the sp 2 -hybridization is deformed. Very recently, we showed that not only the C ohs structure, but also stable ohs monolayers of other group IV elements (Si, Ge), group IV–IV (SiC, GeC, SnC), III–V (BN, BP, BAs, BSb, AlN, AlP, GaN, InN), and II–VI (ZnSe) compounds and their multilayers, as well as 3D periodic ohs crystals, can be regarded a new class of materials like their counterparts in the honeycomb network. Here, C, Si, and Ge ohs monolayers of group IV elements have been found to be good metals as a consequence of multiple crossing of the Fermi level by p z -bands, in contrast to their Dirac semimetal counterparts in a honeycomb network, namely graphene, silicene, and germanene. Recent studies on the adsorption of adatoms like H, O, C, Si, F, Ti, and Gd on bare C ohs monolayer have predicted various critical effects on the electronic properties. In particular, it has been demonstrated that C and Si ohs monolayers can acquire novel magnetic and electronic states. These functional properties are tunable by the coverage of diverse adatoms, by the formation of vacancy and other point defects .…”
Section: Introductionmentioning
confidence: 99%
“… 19 It should be emphasized that such a porous d-GeC monolayer with semiconducting property is rarely found. However, the structure exists in the form of purely carbon-based structures called biphenylene carbons 20 or graphenylenes. 22 These structures occur in various allotropes with a well-ordered ring composed of 8, 10, or 12 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned hydrogenation and halogenation methods, other researchers have also investigated the effects of doping with O, C, NH 3 , CH, CO, NO 2 , and Si on the electronic properties of biphenylene. 17,33,34 Previous studies have mostly focused on the effects of different doping strategies on the electronic properties of biphenylene, as well as comparisons of different doped configurations for stability. In order to fully utilize the properties of biphenylene for eventual semiconductor technology applications, further theoretical investigation is imperative.…”
Section: Introductionmentioning
confidence: 99%